Factor Analysis of the Financial Strain Index from the Welfare, Children and Families: A Three-City Study, Wave 3 - Sally A Hageman; Ji Hyang Cheon (Journal of Financial Therapy, 2023)
This paper uses the Welfare, Children, and Families: A Three-City Study data. The three cities included are Boston, Chicago, and San Antonio. The total sample size was n = 1,773, and almost all respondents were female caregivers (99%). An Exploratory Factor Analysis (EFA) on the financial strain index was conducted because previous research reporting an EFA is limited. The financial strain construct was examined using a Principal Component Analysis (PCA) in two Structural Equation Models (SEMs) and a recursive path analysis estimated by ordinary least squares regression. These previous articles provide the theoretical basis for the EFA reported in this paper. Results of the EFA indicate a one-factor model (RMSEA (.064), CFI (.975), TLI (.958), 2 = 74.995, df = 9, p< .001), and a two-factor model (RMSEA (.035), CFI (.997), TLI (.988), 2 = 12.722, df = 4, p =.0127) are both good fits to the Three-City Study data. However, the one-factor model is more appropriate than the two-factor model based on Eigenvalues and a scree plot. Additional research using the financial strain index from the Three-City Study with samples from different populations is needed to further support retaining a one-factor model. The financial strain index is a valuable composite measure summarizing responses for several rank-ordered items measuring the concept of financial strain. We recommend that financial therapy practitioners use the financial strain index as a one-factor measurement tool to assess client financial strain.
Keywords: financial strain; exploratory factor analysis; Three-City Study